1999
DOI: 10.1177/0533316499321007
|View full text |Cite
|
Sign up to set email alerts
|

There's no Point Raging on Your Own: Using Art Therapy in Groups for People with Eating Disorders

Abstract: This article is an outline of our work running art therapy groups for people with eating disorders. We aim to show that the process of group art therapy, with its unique interplay between making art objects and coming together as a group, can be of therapeutic value to these patients. We look at ways in which both art materials, and the images that the group members produce, are used together with the psychodynamics of the group process. Within this, we explore the movement between concrete expression in art, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Yalom (2005) noted that changing through group psychotherapy was a complicated process and that changes occurred through the mutual interaction between the associated experiences of many people (Yalom 2005). A study that examined the effects of art psychotherapy groups in EDs found factors related to interpersonal learning, emotional expression and group commitment to be effective (Johnson and Parkinson 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Yalom (2005) noted that changing through group psychotherapy was a complicated process and that changes occurred through the mutual interaction between the associated experiences of many people (Yalom 2005). A study that examined the effects of art psychotherapy groups in EDs found factors related to interpersonal learning, emotional expression and group commitment to be effective (Johnson and Parkinson 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Case vignette ( 16) Amari (1986); (Conroy et al, 1986); Crowl (1980); Fitzsimmons and Levy (1997); Fleming (1989); Johnson and Parkinson (1999); Luzzatto (1994); Matto (1997); Misluk-Gervase (2020); Morenoff and Sobol (1989); Murphy (1984); Rust (1994); Schaverien (1994); Sporild and Bonsaksen (2014); Ticen (1990); Wolf et al (1985) Did not report on our outcome measures (7) J o u r n a l P r e -p r o o f…”
Section: Studiesmentioning
confidence: 99%
“…Group members may not be able to tolerate the emotional or psychological content of their own artwork, but others may profit from viewing and responding to it (Johnson and Parkinson, 1999). In the case example, Emma sat quietly for a long time, listening to the other group members discuss her picture.…”
Section: Psychological Workmentioning
confidence: 99%